2013
DOI: 10.1128/aac.01718-12
|View full text |Cite
|
Sign up to set email alerts
|

Activities of Fosfomycin, Tigecycline, Colistin, and Gentamicin against Extended-Spectrum-β-Lactamase-Producing Escherichia coli in a Foreign-Body Infection Model

Abstract: Limited antimicrobial agents are available for the treatment of implant-associated infections caused by fluoroquinolone-resistant Gram-negative bacilli. We compared the activities of fosfomycin, tigecycline, colistin, and gentamicin (alone and in combination) against a CTX-M15-producing strain of Escherichia coli (Bj HDE-1) in vitro and in a foreign-body infection model. The MIC and the minimal bactericidal concentration in logarithmic phase (MBC log ) and stationary phase (MBC stat ) were 0.12, 0.12, and 8 g/… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
69
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 104 publications
(76 citation statements)
references
References 56 publications
4
69
1
Order By: Relevance
“…However, the clinical relevance of developing resistance has been recently questioned (6,7). Further, recent data from preclinical studies have shown that FOF is effective for the treatment of biofilm-associated infections when combined with other classes of antibiotics (8)(9)(10). However, data on the efficacy of FOF monotherapy for the treatment of implant-associated infections in osseous tissue are limited.…”
mentioning
confidence: 96%
“…However, the clinical relevance of developing resistance has been recently questioned (6,7). Further, recent data from preclinical studies have shown that FOF is effective for the treatment of biofilm-associated infections when combined with other classes of antibiotics (8)(9)(10). However, data on the efficacy of FOF monotherapy for the treatment of implant-associated infections in osseous tissue are limited.…”
mentioning
confidence: 96%
“…Furthermore, fosfomycin and daptomycin are currently being investigated and might be promising candidates in the fight against foreign-body-related infections (219)(220)(221). In the case of prosthetic joint-related infection (PJI), in vivo models led to the demonstration that fluoroquinolones exhibited more penetration into the site of infection (222).…”
Section: Currently Used Approaches Do Not Specifically Target Biofilmmentioning
confidence: 99%
“…Several experimental studies (in vitro and biofilm infection models) showed that fosfomycin, alone or in combination with other antibiotics, not only reduced or eradicated clinically significant bacteria from biofilms (26)(27)(28)(29)(30) but also resulted in modifications of the biofilm structure. In a rat cellulose-pouch methicillin-resistant Staphylococcus aureus (MRSA) biofilm model, combination therapy with vancomycin and fosfomycin resulted in the disappearance of biofilm-like structures (31).…”
Section: Activity In Biofilmsmentioning
confidence: 99%
“…However, antagonism between colistin and fosfomycin against OXA-48-producing K. pneumoniae isolates was reported (checkerboards were used) (156). Regarding E. coli, the data refer to ESBL-producing strains; synergy was reported with carbapenems (by checkerboards, timekill assays, and Etest), aztreonam (by checkerboards and time-kill assays), colistin (by time-kill assay and Etest), netilmicin (by Etest), and tigecycline (by time-kill assays and Etest) (28,59,152,153,157). In addition, synergy was reported with cefoxitin (by time-kill assays) at concentrations equal to the MIC of the isolate but not at higher concentrations (157).…”
Section: Newer Studiesmentioning
confidence: 99%